A Comparative Anatomical Study among Some Cultivars of Vitisvinifea L. in Iraq - Aseel Kadim Al-Anbari (Journal of Global Pharma Technology, 2018)
The anatomies of ten cultivars of Vitis in Iraq were studied. leaf epidermal characters and petiole anatomy, We carried out to the leaf covered with cuticle, Multi cellular spine trichomes are present on abaxial surface on taxa under study, epidermis cells were uniseriate, irregular or polygonal shaped in both abaxail and adaxial, in abaxial view we can recognize three types of crystals (druses, raphides, and solitary crystals) in all taxa, Hypostomatic leaf with pentacytic type in most cultivars, but isolated V.v.cv Alajami and V.v.cv. Behrezi with Anomocytic type. Bifacial leaf with different rate of cortex. There are two vascular bundles small and big, the big vascular bundle divided into three shapes; crescent, U, and Cordate shape. Small bundles isolated according the numbers of bundles were 5-10 bundles. Petioles shape could be separate in the cultivars to Semicircular, Oval and Pear shape. The epidermis with crystals occur on the epidermal surfaces of all the cultivars, multicelluertrichomes was founded in the V.v.cv Alajami, V.v.cv. Behrezi, and, V.v.cv. Shaida, the ground tissue which include of several layers of clorenchyma then Varying sizes of parenchyma cells have a huge area of cortex. Vascular bundle in petioles which showed semi complete loop, and separate loop. The data of our study cleary show that epidermal features could be employed to isolated closely related taxa , our finding have been used as veritable taxonomical tool.Keywords: Vitis, Vitis's cultivars, Comparative anatomy, Iraq's grapevine.